Crossroads and Barriers on the Roman Border: Institutional Authority, Roman Heritage and the “Đerdap” Projects - Tatjana B. Cvjetićanin (University of Belgrade, 2020)
Institutional authority, Roman heritage and the “Đerdap” projects